Variability of indian monsoon and its forcing mechanisms since late quaternary - Chen, Liang; Guan, Yulong; Zhou, Liang; Yin, Zhengxin; Jiang, Zhaoxia (Frontiers in Earth Science, 2022)
The Indian monsoon is an important part of the global monsoon system, allowing important transfers of moisture at a large geographical scale and deeply affecting human populations and economic prosperity of regions. The tropical summer monsoon in the northern hemisphere (NH) is generally considered to be driven by low latitude solar radiation, therefore, the summer monsoon strength has near zero-phase relative to the maximum of Northern Hemisphere summer Insolation (NHSI). However, the records from the Arabian Sea and some other parts of the Indian Ocean (e.g., Andaman Sea) show that a ~8 kyr phase difference exists between the Indian summer monsoon (ISM) strength and the NHSI, which is obviously different from the records of stalagmites in the East Asia and other marine sediments (e.g., Bay of Bengal). This leads to the “sea-land precession phase paradox” in ISM research. This paper systematically summarizes the Indian monsoon variability on orbital scale indicated by various records from the Indian monsoon affected areas (including oceans and continents) since the late Quaternary. The orbital forcing of Indian monsoon, the potential phase differences between ISM and NHSI and its possible forcing mechanism are further discussed. The observed phase lag between ISM and NHSI may be controlled by the Atlantic Meridional Overturning Circulation (AMOC), latent heat transfer between the southern Indian Ocean and the Asian continent, or caused by the lack of tightly coupling between the Arabian Sea summer monsoon proxies and the monsoon intensity. In addition, it is still unclear whether the previous monsoon proxies can provide a strong constraint on the intensity of the summer monsoon. Environmental magnetism has been widely used in high-resolution dating and the analysis of paleoclimate variabilities in marine and terrestrial sediments, due to its high sensitivity on the rainfall and temperature. Therefore, in order to solve these issues, it is necessary to combine magnetic parameters with geochemical and paleontological parameters for more systematic work in the future.